Textile antennas for body-centric communication systems : : doctoral thesis - Ivšić, Branimir (B. Ivšić ; Fakultet elektrotehnike i računarstva, 2013)
ABSTRACT: The development of personal body-centric communication systems is an important part of the new generation of wireless communication systems, and one of the recent challenges of communication science and technology. An inevitable part of any such system are antennas, which are required to ensure the wireless transfer of the signal, either within or outside the body, depending on the application. This doctoral thesis deals with the design of small wearable antennas and studying their performance in the body-centric environment by focusing on the specific characteristics of such an environment compared to free space. Several antenna prototypes were realized, and their performance was tested on the body of a human volunteer, as well as on a liquid muscle-equivalent phantom. The influence of bending and moisture in the textile substrate was researched. It was found that bending in the E-plane and low moisture content have a significant influence on the antenna characteristics. The body-centric environment is modelled analytically by calculating Green’s function in the spectral domain for a circular cylinder, and modelling the propagation around the torso using creeping waves. In the next stage, conductive threads and yarns were researched and utilized to make the conductive part of the antenna. A conductive mesh embroidered into some conventional fabric was found to be a simple method enabling both the desired conductivity, and the adequate properties of clothes to be retained. The use of a metallic button was found to be suitable for feeding, both from the aesthetical and functional points of view. Based on those findings, a general strategy for the realization of wearable antennas is proposed, and a full-textile prototype PIFA antenna has been designed, and shown to operate properly. -